Magic mirror on the wall: Cross-buying at the point of sale - Carsten D. Schultz; Björn Gorlas (Electronic Commerce Research, 2023)
Stationary retailers may introduce new technologies, such as augmented reality, to provide product information and recommendations and thus improve shopping experience. Examples of such augmented reality applications are magic mirrors that enable virtual try-on and may induce cross-buying intention. Based on an experimental scenario and the corresponding results from 301 questionnaires, we find that magic mirrors positively impact consumers' cross-buying intention. Cross-buying behavior depends particularly on price attractiveness and the aesthetic appeal of the products. Further, men place less emphasis on price attractiveness when considering cross-buying options than women. Whereas magic mirrors reduce the relationship between perceived product benefits and cross-buying behavior, the technology increases the positive effect of perceived convenience on consumers' buying behavior. Magic mirrors, thus, improve convenience but hinder the perception of product benefits – these are better communicated by sales assistants. Magic mirrors may only partly replace sales staff, but retailers can combine both to serve consumers better.
Keywords: 380; Augmented Reality; Cross-Buying; Magic Mirror; Point of Sale; Retailing